The Dual Mediation Effect of Satisfaction with the Quality of Service and Satisfaction with Resident in the Relationship between Subjective Health and Depression among the Elderly in Long-Term Care Facilities (Medico Legal Update, 2019)
This study aimed to investigate whether satisfaction with the quality of service and satisfaction with residentmediate the relationship between subjective health and depression. Toward this end, the following researchquestions were set. First, what is the correlation between satisfaction with the quality of service, satisfactionwith resident, subjective health, and depression? Second, does satisfaction with the quality of service andsatisfaction with resident mediate the relationship between subjective health and depression? The surveywas conducted by visiting the nursing homes that allowed this study after a phone call request. Face-to-faceinterviews with the elderly people in the institutions were done by the investigator and trained graduatestudents. The survey was completed with 381 elderly people in long-term care facilities (Jan ~ Feb 2017).The analysis of frequency, reliability, and correlation was done using the SPSS PC+ Win. 23.0programs. Themediation analysis and bootstrapping were done using the SPSS PROCESS macro program (model 6). Thisstudy found out that, in the effect of physical health on depression, satisfaction with the quality of serviceand satisfaction with resident have dual mediating effects. These findings were, first, the worse subjectivehealth is, the higher depression is. Second, raising their satisfaction with the quality service provided byfacilities can reduce their depression. Third, because satisfaction with resident can also reduce depression,it is necessary to lead the elderly to adjust themselves to the facilities, and to increase their residentialsatisfaction, which will reduce depression. First, by encouraging those in facilities to participate in varioushealth programs and take care of their diets and by giving proper treatment, it is necessary to improve theirhealth, which will reduce their depression. Second, by providing various environmental, physical, and socialservices which fit the demands of the elderly, it is possible to reduce their depression.